Keep ecological restoration open and flexible - Higgs, Eric S.; Harris, Jim A.; Heger, Tina; Hobbs, Richard J.; Murphy, Stephen D.; Suding, Katharine N. (Nature Publishing Group, 2018)
The stakes are high as investment commitments to ecological restoration intensify1. The ‘international standards’ published by the Society for Ecological Restoration (SER)2 and the adoption of a narrow definition of restoration by the United Nations Convention to Combat Desertification (UNCCD)3 are indications that restoration is moving away from the open and flexible approach that we believe is needed to address responsible intervention in times of rapid change.